Nível de atividade física, comportamento sedentário e teste de caminhada de 6 minutos em crianças e adolescentes com anemia falciforme - Lima, Hugo Nivaldo Melo Almeida (2019)
Introduction: Sickle cell anemia (SCA) is a genetic disease with clinical and epidemiological relevance. Several clinical manifestations are commonly observed in patients with SCA, and these manifestations appear to be associated with reduced ability to exercise. Objectives: To identify the levels of physical activity, sedentary behavior and functional capacity of children and adolescents with AF compared to healthy individuals. In addition, we aimed to establish the determinants of the maximum distance covered in the 6-minute walk test, as well as to create and test an equation to predict this variable in the study population. Materials and methods: This is a cross-sectional study with a quantitative approach. Patients were considered eligible following strict inclusion and exclusion criteria. The participants' identity and rights were preserved, in compliance with Resolution No. 510 of 2016 of the National Health Council. Hematological data were extracted from the patient's chart. After the measurement of the anthropometric measures, the participants, with the help of their respective leaders, answered the Physical activity questionnaire for older children and adolescents. The 6-minute walk test was performed according to the recommendations of the American Thoracic Society. To measure the levels of physical activity, the tri-axial accelerometer AtciGraph wGT3X-BT was used. Quantitative variables were expressed as mean, standard deviation and minimum and maximum range. Categorical variables were expressed as percentages. SPSS software version 13.0 was used. Results: A total of 57 patients were studied. The multivariate analysis resulted in the following equation that predicts the maximum distance covered in the 6-minute walk test: Maximum distance traveled = 487.7 (age × 18.3) - (12 × body mass index). There was no significant difference in distance between patients (500.6 ± 88.7 m) and controls (536.3 ± 94 m). It evidenced the lowest level of physical activity for the group of patients, specifically in performing moderate and vigorous physical activities. Conclusion: Children and adolescents with SCA presented lower level of physical activity, higher sedentary behavior and lower functional capacity, compared to a control group.